ESTIMASI SISTEM ORDE DUA DENGAN MENGGUNAKAN PERANGKAT LUNAK MATLAB - Wahjudi, Rudy S (Jurnal Teknik Elektro, 2001)
Generally, the design of control system begins with plant modeling. The analytical systemmodeling through physical observation is usually dificult to be obtained.Therefore, theexperimental system model become main stay alternative. This paper presents the process ofsystem parameters estimation. The methode of parameters estimation are useâPROGRESIVE ITEGRATION METHODEâ. The resulted of parameters estimation thenbe simulated to computer with used MATLAB software version 5.3. From the result ofsimulation can be showed that the change of system parameters only influencial systemresponnse if the happen of parametera change on the moment transient state systemKeywords: parameter estimation, progressive integration and simulation